Pengembangan Multimedia Interaktif pada Mata Kuliah Manajemen Konstruksi di S1 Pendidikan Teknik Bangunan Universitas Negeri Jakarta - Rr Indra Tanie Kusuma Negara (LPPM Universitas Negeri Jakarta, 2019)
This study is aimed to develop multimedia interactive for Construction Management Course to facilitate student’s learning and also assist the lecturer. Methodolgy used for this research is Research and Development (RnD). Multimedia interactive that is developed using Tutorial Model purposed to be a complement of student’s learning. This research is done with using Lee and Owen (2004) Development Model. Collecting data technique for this study is using questionnaire. The result of this Reasearch and Development (RnD) is ten multimedia interactive. The multimedia interactive is stated “very worthy” by media experts with score 90,68% and also stated “very worthy” by material experts with score 81,64%. The percentage showed that multimedia interactive is ready to be implemented for Construction Management Course.